2014
DOI: 10.5812/numonthly.15224
|View full text |Cite
|
Sign up to set email alerts
|

Serum Cystatin C as a Marker of Renal Function in Critically Ill Patients With Normal Serum Creatinine

Abstract: Background:Serum creatinine as a classic marker of renal function has several limitations in the detection of renal dysfunction.Objectives:This study assessed the validity of serum cystatin C as a marker of renal function in critically ill patients with normal serum creatinine.Patients and Methods:Eighty adult patients referred to intensive care units with serum creatinine levels < 1.5 mg/dL and without hemodynamic instability were chosen and their serum creatinine and cystatin C levels were measured. A 24-hou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
14
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 42 publications
2
14
0
1
Order By: Relevance
“…The combination of the hybridoma technique and phage display technology for screening of paired antibodies provides a new solution, with great biological and clinical significance. The cystain C as a biochemical marker or predictor of GFR offers the greater sensitivity in detecting an abnormal GFR [ 41 , 42 ]. The present study provides the new measurement of GFR to monitor the occurrence and progress of renal diseases.…”
Section: Discussionmentioning
confidence: 99%
“…The combination of the hybridoma technique and phage display technology for screening of paired antibodies provides a new solution, with great biological and clinical significance. The cystain C as a biochemical marker or predictor of GFR offers the greater sensitivity in detecting an abnormal GFR [ 41 , 42 ]. The present study provides the new measurement of GFR to monitor the occurrence and progress of renal diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies demonstrated the superiority of serum cystatin C over creatinine in detecting minor GFR reduction. 25) In addition, estimated GFR or Ccr calculated using cystatin C predicts vancomycin trough levels better than Ccr calculated by Cockcroft-Gault formula. 26,27) In fact, the mean estimated GFR (69.1±33.1 mL/min) 26) or Ccr (46.6±24.6 mL/min) 27) calculated using cystatin C levels before DRPM administration tended to be lower than the mean Ccr calculated by Cockcroft-Gault formula (76.0±37.4 mL/min).…”
Section: Discussionmentioning
confidence: 99%
“…Cystatin C exhibited better accuracy than creatinine in the identifi cation of acute kidney dysfunction in the intensive care setting [19], and it was an early marker of AKI [20,21]. However, similarity between these two markers was observed, even for the early detection of AKI [22,23].…”
Section: Introductionmentioning
confidence: 99%